Intracellular Regulation of Matrix Metalloproteinase-2 Activity: New Strategies in Treatment and Protection of Heart Subjected to Oxidative Stress - Grzegorz Sawicki (Scientifica)
Much is known regarding cardiac energy metabolism in ischemia/reperfusion (I/R) injury. Under aerobic conditions, the heart prefers to metabolize fatty acids, which contribute to 60–80% of the required ATP. During ischemia, anaerobic glycolysis increases and becomes an important source of ATP for preservation of ion gradients. With reperfusion, fatty acid oxidation quickly recovers and again predominates as the major source of mitochondrial oxidative metabolism. Although a number of molecular mechanisms have been implicated in the development of I/R injury, their relative contributions remain to be determined. One such mechanism involves the proteolytic degradation of contractile proteins, such as troponin I (TnI), myosin heavy chain, titin, and the myosin light chains (MLC1 and MLC2) by matrix metalloproteinase-2 (MMP-2). However, very little is known about intracellular regulation of MMP-2 activity under physiological and pathological conditions. Greater understanding of the mechanisms that govern MMP-2 activity may lead to the development of new therapeutic strategies aimed at preservation of the contractile function of the heart subjected to myocardial infarction (MI) or I/R. This review discusses the intracellular mechanisms controlling MMP-2 activity and highlights a new intracellular therapeutic direction for the prevention and treatment of heart injury.